Innovative Idea of Making an 8-Piece Collector by Controlling the Electrodes and Improving Texture of Nanofibers in Electrospinning - Shahaboddin Azimi Yancheshmeh, Hamid Montazerolghaem (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we report the activity of an electrospinning collector that can collect at the same time as controlling the angles and alignment of spun nanofibers. First, electricity is applied to the electrodes to which the electrospinning polyacrylonitrile (PAN) nanofibers are to be absorbed; connected. The new idea for making an 8-electrode collector without rotation is that each of these electrodes works separately with a separate power input wire. This is because the power inside each of the electrodes is connected and disconnected separately so that the input current of the collector can be adjusted with this technique. The main point of success of this method is the use of a collector, consisting of 8 electrodes of a conductive shape, which are separated by cross-section insulation to charge PAN nanofibers, stretch along the gap and form a regular arrangement. Using this method to modify the electrospinning device and better align the nanofibers in regular structures, their performance can be improved to make electrospinning operations easier and more orderly, in controlling the alignment and angles of the nanofibers.